2020
DOI: 10.1542/peds.2019-2379
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Prediction Rule for Mortality in Congenital Diaphragmatic Hernia

Abstract: BACKGROUND: Congenital diaphragmatic hernia (CDH) is a rare congenital anomaly with a mortality of ∼27%. The Congenital Diaphragmatic Hernia Study Group (CDHSG) developed a simple postnatal clinical prediction rule to predict mortality in newborns with CDH. Our aim for this study is to externally validate the CDHSG rule in the European population and to improve its prediction of mortality by adding prenatal variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Possibly this could be explained by the different definitions of postnatal outcome parameters (number of days of ventilation vs. presence of CLD) in their study compared to our study and previous studies. 33 In addition, the same effect was seen for Grades 2 and 3 and gastrointestinal outcomes. These results seem in concordance with Cordier et al.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Possibly this could be explained by the different definitions of postnatal outcome parameters (number of days of ventilation vs. presence of CLD) in their study compared to our study and previous studies. 33 In addition, the same effect was seen for Grades 2 and 3 and gastrointestinal outcomes. These results seem in concordance with Cordier et al.…”
Section: Discussionmentioning
confidence: 72%
“…In contrast, the incidence of need for treatment of PH in our study (45%) is lower than previously reported incidence rates (>60%). These incidences are based, however, on diagnosis of PH by echocardiography, not purely on need for treatment 32–34 . In general, PH is defined as pulmonary pressures higher than two‐thirds of the systemic pressures on echocardiography, measured at the first day of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CDH may present as an isolated anomaly (isolated-CDH) or patients can have one or more additional anomalies (CDH-complex) ( 1 , 31 ). Anomalies can be found in all body sites; cardiac anomalies, anomalies of the urogenital system, limb malformations, nervous system anomalies, orofacial clefts, and gastrointestinal anomalies including intestinal atresia ( 3 , 32 ).…”
Section: Isolated Cdh and Complex Cdhmentioning
confidence: 99%
“…Consequently, this period also enables clinicians a chance to determine the severity of the congenital abnormality by monitoring physiological parameters and/or ventilatory requirements. There are already several scoring systems to determine the risk of adverse outcomes available, such as the Score for Neonatal Acute Physiology-II (SNAP-II) score, Wilford Hall/Santa Rosa prediction model and the Brindle scoring model (36)(37)(38)(39)(40). Most of these scoring systems are combining several clinical parameters (such as blood pressure, serum pH, fraction of inspired oxygen FiO 2 ) yet the majority of these scoring systems use the worst values of the parameters within the first 12-24 h (37)(38)(39).…”
Section: Early Predictors Of Adverse Outcomementioning
confidence: 99%